2019
DOI: 10.11591/ijece.v9i4.pp2675-2681
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Heart Ailment in Patients with Varying number of Features using Data Mining Techniques

Abstract: <span lang="EN-US">Data mining can be defined as a process of extracting unknown, verifiable and possibly helpful data from information. Among the various ailments, heart ailment is one of the primary reason behind death of individuals around the globe, hence in order to curb this, a detailed analysis is done using Data Mining. Many a times we limit ourselves with minimal attributes that are required to predict a patient with heart disease. By doing so we are missing on a lot of important attributes that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
13
0
1
Order By: Relevance
“…Many research works have shown that Machine Learning algorithms are employed as technologies in Data Mining, which have played an important role in the application of classification, analysis, prediction and pattern recognition on many health issues [33][34][35][36]. Especially in diagnosis of disease, such as the cancer, heart, diabetes and Alzheimer disease, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many research works have shown that Machine Learning algorithms are employed as technologies in Data Mining, which have played an important role in the application of classification, analysis, prediction and pattern recognition on many health issues [33][34][35][36]. Especially in diagnosis of disease, such as the cancer, heart, diabetes and Alzheimer disease, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent years, the amount of data in the healthcare centers is large. Machine learning algorithms are widely applied to the larger medical datasets to discover interesting pattern and knowledge from the dataset and automate disease diagnosis with predictive model [4][5][6][7]. One of the approach for discovering important pattern from a medical dataset is exploring the relationships among dataset features.…”
Section: Introductionmentioning
confidence: 99%
“…The cranial vessels for smell and vision originate in the cerebrum. Therefore, good blood circulation in the vessels Int J Artif Intell ISSN: 2252-8938 Brain stroke computed tomography images analysis using image processing: A review (Nur Hasanah Ali) 1049 is important to avoid neuronal damage and subsequent neurological deficits that will lead to cell death [3], [4].…”
Section: Introductionmentioning
confidence: 99%